Effect Of Bad Debt, Market Capitalization, Operation Cost, Capital Adequacy, Cash Reserves On Financial Performance of Commercial Banks In Bahrain - Salem Oudat, Mohammad (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study to examine the effect of bad debt, market capitalization, operation cost, capital adequacy, cash reserves on financial performance. The analysis was conducted to collect the essential data from the annual reports of 7 commercial banks listed in Bahrain Bourse for the period 2014 to 2018. Panel data analysis is employed with a total number of 35 observations. The results of the multiple regression analysis with Pooled OLS revealed that all independent variables; non-performing loans, operating costs, cash reserve, and also capital adequacy have a positive and significant relationship with the financial performance. While only market capitalization has an insignificant relationship with financial performance. This study therefore this study recommends that the management of commercial banks in Bahrain should strive to reduce as much as possible the nonperforming loans (bad debt) .also the management of commercial banks to improve the volume and value of assets at its disposal.